1984
DOI: 10.3109/15563658408992563
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Chlorophenates: Toxicology and Respiratory Effects

Abstract: We have identified 71 chlorophenate-exposed sawmill workers as part of a group undergoing an extensive health and environmental evaluation in a pulp mill. We have compared this group with a group (351) with no physical proximity to the area in which chlorophenates were used. We demonstrated a gradient of exposure from 230 ppb in urine and 919 ppb in serum for those directly handling the contaminated wood, to 139 ppb in urine and 354 ppb in serum for those working in the area but not in manual contact as compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The chronic effects of exposure to PCP have been studied in PCP production workers (4-10), PCP formulators (11), wood treatment workers (12,13), sprayers (11), and sawmill workers (14)(15)(16). Several studies have demonstrated that exposure to commercial PCP can produce chloracne (4,8-10,17,18).…”
mentioning
confidence: 98%
“…The chronic effects of exposure to PCP have been studied in PCP production workers (4-10), PCP formulators (11), wood treatment workers (12,13), sprayers (11), and sawmill workers (14)(15)(16). Several studies have demonstrated that exposure to commercial PCP can produce chloracne (4,8-10,17,18).…”
mentioning
confidence: 98%